Ultra high gain step up DC/DC converter based on switched inductor and improved voltage lift technique for high‐voltage applications - Shahrukh Khan (13791895) (2022)
Voltage lift is a well‐known technique to improve the voltage gain of the converter. A combination of switched inductor and the conventional voltage lift technique can be used to achieve high gain, but the semiconductor's stress is still high. An improved voltage lift technique by employing an extra diode and capacitor and a switched inductor is proposed, which significantly increases the voltage boosting factor and reduces the voltage stress of semiconductor devices. The proposed converter is transformerless and non‐isolated in nature. The proposed topology has a continuous input source current and has a common connection between the source and the load. The converter is controlled by a single switch, making it simple to use. The steady‐state relations are drawn out in both continuous conduction mode (CCM) and discontinuous conduction mode (DCM). The effect of the unequal inductance on the voltage gain is carried out in detail. The improved voltage lift technique can develop the n‐stage converter to improve voltage gain further and reduce stress on semiconductors. The proposed topology is compared with the recent converters, and the effect of the non‐idealities on the voltage gain and losses occurring in the components is discussed in detail. A hardware prototype with a rating of 20V/300V, 250 W is built to test the suggested topology's performance and theoretical analysis. At a 20‐V input, the highest efficiency was measured to be 95.8%. Other Information Published in: IET Power Electronics License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1049/pel2.12279